2017
DOI: 10.1016/j.ejrad.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The Evans’ Index revisited: New cut-off levels for use in radiological assessment of ventricular enlargement in the elderly

Abstract: The range of the EI measurements in healthy elderly is wide, and a cut-off value of 0.3 cannot be used to differentiate between normal and enlarged ventricles in individual cases. The proposed EI thresholds from the present study show good sensitivity for the iNPH diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 30 publications
4
85
3
Order By: Relevance
“…[ 5 ] In our recent study, iNPH patients with EI ≤0.3 was observed at 30% and with non-DESH at 55% of 84 definite iNPH patients. [ 6 ] Similar results have been reported from other laboratories suspecting the reliability of DESH[ 7 8 ] Regarding EI, 29% of healthy elderly people have EI >0.3,[ 9 ] and there is no clear basis for using EI >0.3 as an index of ventriculomegaly, and it is inconsistent. The cases have been also reported that the symptoms were improved by CSF shunting despite EI ≤0.3.…”
Section: Introductionsupporting
confidence: 72%
“…[ 5 ] In our recent study, iNPH patients with EI ≤0.3 was observed at 30% and with non-DESH at 55% of 84 definite iNPH patients. [ 6 ] Similar results have been reported from other laboratories suspecting the reliability of DESH[ 7 8 ] Regarding EI, 29% of healthy elderly people have EI >0.3,[ 9 ] and there is no clear basis for using EI >0.3 as an index of ventriculomegaly, and it is inconsistent. The cases have been also reported that the symptoms were improved by CSF shunting despite EI ≤0.3.…”
Section: Introductionsupporting
confidence: 72%
“…A combination of abnormal MTA and GCA also have a greater sensitivity and specificity for AD [15]. Evans’ index has been shown to increase with age but there is no significant difference between heathy elderly and patients with AD [22]. We believe that our results emphasize that MTA and PCA should be reported why we find the severe underreporting of MTA and PCA to be remarkable.…”
Section: Discussionmentioning
confidence: 61%
“…It gives an estimation of the size of the lateral ventricles and indirect estimation of central atrophy. Evans’ index was originally based on encephalographic measurements but has been modified for axial CT. New cut-offs corrected for age and gender have been proposed as follows (age, males/females): 65–69 years 0.34/0.32, 70–74 years 0.36/0.33, 75–79 years 0.37/0.34, and 80–84 years 0.37/0.36 [22]. For patients < 65 years EI ≥ 0.30 was considered pathological regardless of gender.…”
Section: Methodsmentioning
confidence: 99%
“…Both the international and the Japanese guidelines define ventricular enlargement as an Evans’ index greater than 0.3 1 , 4 . It has been generally used as an indirect, surrogate marker of ventricular volume 5 7 . Second, volumetric measurements have been recommended to represent an accurate estimate of true ventricular size 8 .…”
Section: Introductionmentioning
confidence: 99%